The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1186/s42834-019-0039-y
|View full text |Cite
|
Sign up to set email alerts
|

Screening potential plant species for arresting particulates in Jharia coalfield, India

Abstract: Mining and related activities cause severe degradation of ambient air quality. A study of particulate matter (PM) across transportation, mining and control (C) sites for dust attenuation capacity (DAC) in selected tree species were carried out in Jharia coalfield (JCF) to estimate the menace of dust pollution and also to measure air pollution tolerance index (APTI). Results indicated that the maximum value of PM 10 and PM 2.5 ranged from 54 to 174 and 29 to 78 μg m − 3 respectively across all the sites. The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…As shown in Figure 5A,B, PM up to 2 µm could enter or block the stomata. Several researchers have reported that more PM could be deposited on rough leaf surfaces [17,26,27]. In particular, when PM (Ag-NP) is adsorbed through the leaves of woody plants, such as poplar.…”
Section: Pm Adsorption Location On Leavesmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 5A,B, PM up to 2 µm could enter or block the stomata. Several researchers have reported that more PM could be deposited on rough leaf surfaces [17,26,27]. In particular, when PM (Ag-NP) is adsorbed through the leaves of woody plants, such as poplar.…”
Section: Pm Adsorption Location On Leavesmentioning
confidence: 99%
“…In particular, when PM (Ag-NP) is adsorbed through the leaves of woody plants, such as poplar. However, it quickly migrates to the stem, increasing the leaves' O 2 −, reducing bio-mass, and affecting bacterial and fungal growth [27]. In addition, the presence of more PM in the leaves reduced the efficiency of the photosynthetic device, lowered the ratio of photosynthesis and chlorophyll, and lowered energy efficiency.…”
Section: Pm Adsorption Location On Leavesmentioning
confidence: 99%
“…It has been found that plants can filter certain pollutants through absorption, adsorption and metabolism [11]. Thus, plants act as an important sink of air pollutants [12]. Deposition rates of air pollutants on vegetation have been found higher than those on the built-up structures [13].…”
Section: Introductionmentioning
confidence: 99%
“…Rain is accompanied by thunderstorms with normal fall in temperature. Average precipitation is 1000-1200 mm from July to September with little in winter [23].…”
Section: 1mentioning
confidence: 99%